Gene 32 protein of bacteriophage T4 moderates the activities of the T4 gene 46/47-controlled nuclease and of the Escherichia coli RecBC nuclease in vivo. - Mosig, G (1976)
Genes 46 and 47 of phage T4 control a nuclease that is required for genetic recombination and may act similarly to the Escherichia coli RecBC nuclease. In vivo, the nucleolytic activities of both of these nucleases must be moderated so that recombining DNA intermediates are not destroyed. We conclude from our present experiments that the phage T4 gene 32 protein, specifically its C-terminal domain, participates in such moderation. We have investigated DNA degradation in different gene 32 and gene 32/46 mutants under conditions that are completely restrictive for progeny production in all the mutants. Under these conditions, DNA of those gene 32 mutants in which the C-terminal domain of the protein is not synthesized or is modified is degraded to acid-soluble material. T4 gene 46 or E. coli recB mutations reduce such degradation; together they abolish it completely. By contrast, single gene 32 mutants which produce an unaltered C-terminal domain show little or no degradation of their DNA. Residual protection against nucleases is unrelated to residual primary DNA replication or to overproduction of the mutant peptides in the different gene 32 mutants.